Gender and the Negotiation of Daily Life in Mexico, 1750-1856 - Lipsett-Rivera, Sonya, 1961- (Book collections on Project MUSE., 2012)
History is not just about great personalities, wars, and revolutions; it is also about the subtle aspects of more ordinary matters. On a day-to-day basis the aspects of life that most preoccupied people in late eighteenth- through mid nineteenth-century Mexico were not the political machinations of generals or politicians but whether they themselves could make a living, whether others accorded them the respect they deserved, whether they were safe from an abusive husband, whether their wives and children would obey them--in short, the minutiae of daily life. Sonya Lipsett-Rivera's Gender and the Negotiation of Daily Life in Mexico, 1750-1856 explores the relationships between Mexicans, their environment, and one another, as well as their negotiation of the cultural values of everyday life. By examining the value systems that governed Mexican thinking of the period, Lipsett-Rivera examines the ephemeral daily experiences and interactions of the people and illuminates how gender and honor systems governed these quotidian negotiations. Bodies and the built environment were inscribed with cultural values, and the relationship of Mexicans to and between space and bodies determined the way ordinary people acted out their culture.